Análise de contaminações microbiológicas em laboratórios de pesquisa da Universidade Federal do Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The present work aims to analyze the microbial contamination in laboratories of the Universidade Federal do Oeste do Pará. The collections were carried out in 3 UFOPA laboratories. The collections were carried out on benches, laminar flow ovens. For this purpose, swabs were used that were rubbed in an area of 10cm2 and inoculated in TSA and MacConkey ágar. After incubation the colonies were counted and the different morphotypes were isolated and identified by microscopic analysis, PCR and sequencing. After identification microorganisms with pathogenic potential, they were submitted to an antibiogram. At the end of the laboratory analyses, a total of 920 microorganisms were found with 20 different species between bacteria and fungi identified. Three species stand out for not being found in university laboratories with a certain frequency, they are: Klebsiella pneumoniae, Corynebacterium pseudodiphtheriticum and Acinetobacter baumannii. In the present analysis, it was found that high percentages of bacteria and fungi found were present in all laboratories, that did not meet the parameters recommended by the PAHO, which proves that the hygienic conditions of benches, laminar flows and ovens must be improved to minimize the risks of infections and contaminations in experiments that are carried out. It was concluded from the analyzes that all laboratory environments presented microbial contamination, although there was some variation between environments. It is necessary to standardize disinfection protocols and good laboratory practices as a whole.
Keywords: Microrganismo; Contaminação Bacteriana; Limpeza; Laboratórios da UFOPA; CNPQ:: CIÊNCIAS BIOLÓGICAS